Seção participe de zerohora.com: estratégias de ofertas de vínculos no webjornalismo - Teixeira, Luana Goulart (Universidade do Vale do Rio dos Sinos, 2011)
This dissertation examines increasingly complex strategies taken by media organizations in the search for new interactions that promote the link with the reception. In examining Section Participe of zerohora.com, a device that performs the interations of the web journal with its readers, observed the formation of a contract that brings reading discursive regimes crossed by the effects of media coverage of journalism. Through a process analytical-descriptive noted, among other things, that the contract is read Section Join a rational development of productive niche as it seeks results, although not always to be effective in terms which are estimated. When make six blocks of the array of reading contract examined, we can say that this is a contract arranged through separate operations with some other objectives and strategies designed to reach distincts audiences.
Keywords: Journalism mediatized; Webjournalism; Mediatization; Jornalismo midiatizado; Webjornalismo; Midiatização; ACCNPQ::Ciências Sociais Aplicadas::Comunicação